Student Cognitive Analysis in STEAM-Based Pre-Vocational Experiential Learning at the Elementary Level - Rusdi Febriyanto; Ade Dwi Putra Janata; Ananda Yhuto Wibisono Putra; Ricky Cahyasari Putra; Ikhsanudin Ikhsanudin; R. Ahmad Zaky El Islami; Nguyen Van Bien; Ahmet Selçuk Akdemir (International Journal of STEM Education for Sustainability, 2026)
The Making Indonesia 4.0 program requires an educational system that fosters transdisciplinary, contextual, and practical learning to improve technical literacy and promote environmental sustainability. This study is aimed to assess the effectiveness of STEAM-based pre-vocational experiential learning in improving the cognitive abilities of primary school children. This study employed a quantitative, quasi-experimental One-Group Pretest-Posttest design. The study involved 27 fifth-grade primary school students selected through a purposive sampling technique. The results showed that the average pre-test score for students was 54.70, and most of them fell into the medium range (51–75). After STEAM-based learning was put into place, the average score on the post-test went up to 72.66, and most students moved up to the high group (76–100). According to Hake's criteria (1999), the N-Gain analysis showed an average value of 0.40, which means it was moderate. The Paired Sample t-Test also showed a significance value of p = 5.75 × 10⁻⁷ (0.05), which means that the learning outcomes improved in a statistically significant way. Thus, it can be deduced that STEAM-oriented pre-vocational experiential learning is comparatively beneficial in augmenting students' cognitive abilities. This method positively influences learning outcomes descriptively and is empirically validated, rendering it pertinent for use as a contextual learning technique to enhance 21st-century capabilities in primary education.